Seed and Cone Characteristics of Spruce (Picea smithiana Wall) - A.H. MUGHAL; M. A. KHAN; S. N. ZAFFAR; JAVEED MUGHLOO (Seed Research, 2026)
A study in the non monsoon zone of Jammu and Kashmir relating to cone, seed and germination characteristics of Picea smithiana revealed significant differences among cone and seed parameters. Cones collected from different trees varied in weight, length, diameter as well as specific gravity. The mean cone weight was 94.5 gm at maturity with mean diameter of 37.20 mm and length of 12.85 cm. Specific gravity an index of maturity recorded a mean of 0.96. Seed weight as well as seed number per cone also varied.Seed number per cone recorded an average of 124.60, which accounted for about 1.53% of total cone weight. Seed weight averaged 11.6 gm/1000. Germination study revealed that freshly harvested seeds have dormancy and the same can be overcome by cold stratification. Cold stratification for varying periods of time from 1 to 5 weeks not only increased germination per cent but germination value also recorded an increase and MGT for completion of germination decreased significantly. In the present study 4 week stratification resulted in all round improvement in germination per cent, germination value and mean germination time. Germination per cent and germination value after 4 week of stratification was 80% and 36.05, an increase of 56.86% and 297% over control respectively. Mean germination time recorded after 4 weeks was 12.7 days recording a fall of 8.16 days over control.